1915 Vt. Acts & Resolves 344, No. 205, §§ 1-2. - (:unkn) unknown (General Publisher, 1915)
A person who uses a slungshot, black jack, brass knuckles or similar weapons against another person, or attempts so to do, or is found in possession of a slungshot, black jack, brass knuckles, or similar weapon, with intent so to use it, shall be imprisoned in the state prison not more than five years. A person who within the state manufactures or causes to be manufactured, or sells or gives away or parts with, or offers so to do, or keeps for sale or gift, a slungshot, black jack, brass knuckles, or similar weapons, shall be imprisoned not more than two years or fined not more than five hundred dollars nor less than two hundred dollars."
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - NON-GUN ARMS